STUDY ON PREPARATION AND CHARACTERIZATION OF SACHI SEED OIL BASED EMULSION CONTAINING COLLAGEN PEPTIDES - Thuy Chinh, Nguyen; Dinh Duc, Cung; Ngoc Quynh, Nguyen; Hoang, Thai; Phi Hung, Nguyen; Thi Thu Trang, Pham; Quoc Trung, Vu (HNUE Journal of Science: Journal of Natural Sciences, 2024)
In this study, collagen peptides were carried by a Sacha inchi (sachi) seed oil-based emulsion with Tween 80 under optimal conditions: 26.26% sachi seed oil, 26.06% Tween 80, and 47.68% distilled water. Collagen peptides, varying from 5 - 30% of the total emulsion mass, were dispersed in the aqueous phase before being introduced into the emulsion. Using the sachi seed oil-based emulsion to carry collagen peptides helps prevent the hydrolysis of collagen peptides by acids and enzymes in the digestive system. The characteristics of the emulsion were evaluated using dynamic light scattering, infrared spectroscopy, and ultraviolet-visible spectroscopy. The emulsions loaded with collagen peptides have average droplet sizes ranging from 83.57 - 286.93 nm. Emulsions carrying 5 - 10% collagen peptides exhibit a high stability for up to 30 days. These results demonstrate the potential application of sachi seed oil emulsions carrying collagen peptides in functional foods and healthcare products.